Homologous Recombination Deficiency Alterations in Colorectal Cancer: Clinical, Molecular, and Prognostic Implications. (1st September 2021) - Moretto, Roberto; Elliott, Andrew; Zhang, Jian; Arai, Hiroyuki; Germani, Marco Maria; Conca, Veronica; Xiu, Joanne; Stafford, Phillip; Oberley, Matthew; Abraham, Jim; Spetzler, David; Rossini, Daniele; et al.
Abstract: Background: Tumors with homologous recombination deficiency (HRD) show high sensitivity to platinum salts and poly(ADP-ribose) polymerase–inhibitors in several malignancies. In colorectal cancer (CRC), the role of HRD alterations is mostly unknown. Methods: Next-generation sequencing, whole transcriptome sequencing, and whole exome sequencing were conducted using CRC samples submitted to a commercial Clinical Laboratory Improvement Amendments certified laboratory. Tumors with pathogenic and/or presumed pathogenic mutations in 33 genes involved in the homologous recombination pathway were considered HRD, the others were homologous recombination proficient (HRP). Furthermore, tumor samples from patients enrolled in the phase III TRIBE2 study comparing upfront FOLFOXIRI+bevacizumab vs FOLFOX+bevacizumab were analyzed with next-generation sequencing. The analyses were separately conducted in microsatellite stable or proficient mismatch repair (MSS/pMMR) and microsatellite instable-high or deficient mismatch repair (MSI-H/dMMR) groups. All statistical tests were 2-sided. Results: Of 9321 CRC tumors, 1270 (13.6%) and 8051 (86.4%) were HRD and HRP, respectively. HRD tumors were more frequent among MSI-H/dMMR than MSS/pMMR tumors (73.4% vs 9.5%; P  < .001; q  < 0.001). In MSS/pMMR group, HRD tumors were more frequently tumor mutational burden high (8.1% vs 2.2%; P  < .001; q  < 0.001) and PD-L1 positive (5.0% vs 2.4%; P  < .001; q  = 0.001), enriched in all immune cell and fibroblast populations and genomic loss of heterozygosity-high (16.2% vs 9.5%; P  =   .03). In the TRIBE2 study, patients with MSS/pMMR and HRD tumors (10.7%) showed longer overall survival compared with MSS/pMMR and HRP tumors (40.2 vs 23.8 months; hazard ratio [HR] = 0.66, 95% confidence interval [CI] = 0.45 to 0.98; P  =   .04). Consistent results were reported in the multivariable model (HR = 0.67, 95% CI = 0.45 to 1.02; P  =   .07). No interaction effect was evident between homologous recombination groups and treatment arm. Conclusions: HRD tumors are a distinctive subgroup of MSS/pMMR CRCs with specific molecular and prognostic characteristics. The potential efficacy of agents targeting the homologous recombination system and immune checkpoint inhibitors in this subgroup is worthy of clinical investigation.